Ag2S / Bi2O3 / Bi2S3 photoelectric thin film with recognition performance and preparation method and application of Ag2S / Bi2O3 / Bi2S3 photoelectric thin film

By introducing Ag2S into photoelectric materials, a multi-component ternary heterojunction is formed, and a sensor is constructed in combination with molecular imprinting technology, the shortcomings of existing photoelectric materials in terms of separation efficiency and conversion efficiency are solved, and photocatalysis and electrocatalysis are realized and the versatility of bisphenol A detection.

CN119403282APending Publication Date: 2025-02-07YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411527680.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing photoelectric materials have room for improvement in the complex preparation process, the separation efficiency of electron-hole pairs and the photoelectric conversion efficiency, and it is difficult to achieve both photocatalytic and electrocatalytic functions.

Method used

Ag2S/Bi2O3@Bi2S3 photoactive materials were prepared by low-temperature water bath method and in-situ ion layer adsorption method to form multi-component ternary heterojunctions, and MIP/Ag2S/Bi2O3@Bi2S3/FTO sensors were constructed in combination with molecular imprinting technology to achieve the matching of the MIP/Ag2S/Bi2O3@Bi2S3/FTO sensors. Quantitative detection of bisphenol A.

Benefits of technology

The separation efficiency and photoelectric conversion efficiency of electron hole pairs are improved, the dual functions of photocatalysis and electrocatalysis are realized, and the efficient quantitative detection of bisphenol A is achieved through the MIP-PEC sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005109671090000111
    Figure BDA0005109671090000111
  • Figure HDA0005109671110000011
    Figure HDA0005109671110000011
  • Figure HDA0005109671110000012
    Figure HDA0005109671110000012
Patent Text Reader

Abstract

The invention discloses an Ag2S / Bi2O3 / Bi2S3 photoelectric film with recognition performance as well as a preparation method and application of the Ag2S / Bi2O3 / Bi2S3 photoelectric film. The photoelectric film is a Bi2O3 / Bi2S3 photoelectric film nano material with Ag2S deposited on the surface. A one-step water bath method is adopted to synthesize a Bi2O3 (at) Bi2S3 binary heterostructure, due to a stronger synergistic effect among multi-component substances, the separation efficiency of electron hole pairs is further improved, then Ag2S is introduced through an improved in-situ ion layer adsorption method, Ag2S / Bi2O3 (at) Bi2S3 / FTO is synthesized, and the introduction of Ag2S can effectively prolong the service life of photon-generated carriers, so that the rate of photocatalytic reaction is improved. The MIP / Ag2S / Bi2O3 / Bi2S3 / FTO sensor is constructed through molecular imprinting, the synthesis method is simple and efficient, the cost is low, operation is easy, the sensor construction process is simple and efficient, and the target bisphenol A can be sensitively detected and recognized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance and a preparation method and application thereof, belonging to the technical field of nanomaterials. Background Art

[0002] An interface with photoelectric response and selective recognition ability is the key to building a high-performance photoelectric sensor. Therefore, it is very necessary to prepare a photoelectric film with recognition performance to build a photoelectric sensor, which is an important component of the interface of the photoelectric material.

[0003] Pure Bi2O3 has a weak ability to absorb visible light, resulting in poor photocatalytic activity and carrier separation efficiency, which limits its application and development. The band structures between Bi2O3 and Bi2S3 are well matched, and the conduction band and valence band are staggered, which indicates that it is very likely to construct an efficient heterojunction between them. Bi2O3@Bi2S3 heterostructures can improve the separation of photogenerated electron-hole pairs, but the low activity of binary Bi2O3@Bi2S3 composites makes their practical application very difficult.

[0004] In the field of photoelectrochemical sensing, Professor Mei Xuena's team at Jinan University prepared a near-infrared responsive sea urchin-shaped bismuth sulfide / silver sulfide composite material that can effectively absorb near-infrared radiation and achieve efficient photoelectrochemical conversion. Professor Yuan Ye's team at Harbin Institute of Technology used room temperature solution method and magnetron sputtering to prepare large-area bismuth oxide and bismuth sulfide nanotube array structures, and then constructed photodetectors. However, the preparation process of the above photoelectric materials is complicated, and the separation of electron-hole pairs and photoelectric conversion efficiency still have room for improvement.

[0005] In terms of photocatalysis, Zhao Jin's team at Henan Normal University prepared a hollow spherical β-Bi2O3 / Bi2S3 heterojunction photocatalyst with excellent light absorption performance. With its large specific surface area and pore volume, it can effectively photocatalytically oxidize RhB wastewater and photocatalytically reduce Cr(VI) wastewater under simulated sunlight. Gao Yushu's team at Qinghai Normal University prepared a composite Z-type composite photocatalyst Ag2S / Bi2O3 photocatalyst based on selective modification, which can effectively solve the problem of consuming photogenerated charges in traditional Z-type composite photocatalysts, and catalytically degrade A07 by 98.5%. However, the preparation process of these materials is complicated, and they are only used as photocatalysts, and their role in electricity is still to be developed. Is it possible to develop a photoelectric material that has both photocatalytic and electrocatalytic properties?

[0006] Bismuth sulfide and bismuth oxide are coupled to form a binary heterojunction to replace pure photoelectric active materials, which can effectively enhance the photoactivity and can be used for the efficient separation of electron-hole pairs. However, the binary heterojunction only involves two materials, the combination is relatively limited, the adjustment ability is weak, and there are defects at the interface between the materials. These defects will affect the transmission of electrons and photons. At the same time, the stability of binary heterojunction materials under some high temperature and extreme conditions is relatively limited. In addition, the existing technology for preparing bismuth-based binary heterojunctions is relatively complex and the process is complicated.

[0007] Bisphenol A, as one of the main matrices for producing epoxy resins and polycarbonate plastics, is widely present in many consumer products in daily production and life. However, its toxicity can affect the reproductive and endocrine systems of humans and wild animals. Molecularly imprinted polymers (MIPs) are polymers formed by cross-linking polymerization. They have the ability to specifically recognize targets and have high stability under extreme chemical conditions. As a recognition element, MIPs have great commercial prospects and practical application value in the construction of sensors. Therefore, it is urgent to construct molecular imprinting sensors for bisphenol A detection. Summary of the invention

[0008] Objectives of the invention: The first objective of the present invention is to provide an Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance. The second objective of the present invention is to provide a method for preparing the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance. The third objective of the present invention is to provide an imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO prepared using the Ag2S / Bi2O3@Bi2S3 photoelectric film. The fourth objective of the present invention is to provide a method for preparing the imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO. The fifth objective of the present invention is to provide the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance or the imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO in the detection of bisphenol A.

[0009] Technical solution: The present invention discloses an Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance, wherein the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance is a Bi2O3@Bi2S3 photoelectric film nanomaterial with Ag2S deposited on the surface.

[0010] Furthermore, the preparation method of Bi2O3@Bi2S3 photoelectric thin film nanomaterial comprises the following steps:

[0011] (A1) adding bismuth nitrate pentahydrate to a nitric acid solution and stirring vigorously to obtain a precursor solution A;

[0012] (A2) adding hexadecyltrimethylammonium bromide and thioacetamide to water and mixing by ultrasonication to obtain solution B;

[0013] (A3) Precursor solution A is added dropwise into solution B, stirred, centrifuged, washed, and vacuum dried to obtain Bi2O3@Bi2S3 nanomaterials.

[0014] Furthermore, in step (A1), the solid-to-liquid ratio of bismuth nitrate pentahydrate to nitric acid solution is (0.2300-0.2332): 5.25 g / mL.

[0015] Furthermore, in step (A1), the concentration of the nitric acid solution is 2-5%.

[0016] Furthermore, in step (A2), the mass ratio of hexadecyltrimethylammonium bromide, thioacetamide and water is (0.1200-0.1248):0.0698:60.

[0017] Furthermore, in step (A3), the stirring time is 3 to 3.5 hours and the stirring temperature is 30 to 40°C.

[0018] Furthermore, in step (A3), the centrifugal speed is 6000-8000r, and the centrifugal time is 5-8min.

[0019] Furthermore, in step (A3), washing is performed with water and ethanol respectively.

[0020] Furthermore, in step (A3), vacuum drying is performed at 60-65° C. for 10-12 h.

[0021] The method for preparing the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance of the present invention comprises the following steps:

[0022] (B1) Ultrasonic dispersion of Bi2O3@Bi2S3 photoelectric thin film nanomaterials in water to obtain a dispersion, drop the dispersion on FTO conductive glass, and dry it to obtain a Bi2O3@Bi2S3 / FTO electrode;

[0023] (B2) Drop silver nitrate solution on the surface of the Bi2O3@Bi2S3 / FTO electrode and react in the dark, drop sodium sulfide solution on the surface of the Bi2O3@Bi2S3 / FTO electrode after the reaction, continue the reaction, wash and dry.

[0024] Furthermore, in step (B1), the concentration of Bi2O3@Bi2S3 in the dispersion is 4-5 mg / mL.

[0025] Furthermore, in step (B1), the dispersion liquid is dropped on the FTO conductive glass at a concentration of 15 to 20 uL / cm 2 .

[0026] Furthermore, in step (B2), the concentration of the silver nitrate solution is 20 to 22 mmol / L.

[0027] Furthermore, in step (B), silver nitrate solution is dropped on the FTO conductive glass at a concentration of 15 to 20 uL / cm 2 .

[0028] Furthermore, in step (B2), the concentration of the sodium sulfide solution is 20 to 22 mmol / L.

[0029] Furthermore, in step (B2), sodium sulfide solution is dropped on the FTO conductive glass at 15 to 20 uL / cm 2 .

[0030] Furthermore, in step (B2), the reaction is continued for 30 to 40 minutes.

[0031] An imprinting sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO is prepared by using the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance of the present invention.

[0032] The preparation method of the imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO of the present invention comprises the following steps:

[0033] (C1) dissolving bisphenol A (BPA), methacrylic acid and styrene in N,N-dimethylformamide and stirring; adding ethylene glycol dimethacrylate and azobisisobutyl ester, continuing to stir, degassing, and heating to react to obtain a MIP solution;

[0034] (C2) Mix the MIP solution with an N,N-dimethylformamide solution containing polyvinylidene fluoride, shake vigorously, and drop the mixed solution onto the surface of the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance described in the present invention, dry, soak to remove bisphenol A, wash, and dry to obtain the imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO.

[0035] Furthermore, in step (C1), the molar ratio of bisphenol A, methacrylic acid and styrene is 0.1:(0.2-0.6):0.1.

[0036] Furthermore, in step (C1), the molar mass ratio of ethylene glycol dimethacrylate to azobisisobutyl ester is (1.2-1.6): 20 mmol / mg.

[0037] Furthermore, in step (C1), the stirring time is continued for 10 to 15 minutes.

[0038] Furthermore, in step (C1), degassing is performed with nitrogen for 30 to 35 minutes.

[0039] Furthermore, in step (C1), the heating reaction is carried out at 60-70° C. for 2.5-3 h.

[0040] Furthermore, in step (C2), the volume ratio of the MIP solution to the N,N-dimethylformamide solution containing polyvinylidene fluoride is (90-100):900.

[0041] Furthermore, in step (C2), the concentration of the N,N-dimethylformamide solution containing polyvinylidene fluoride is 3 to 4 mg / mL.

[0042] Furthermore, in step (C2), the time of vigorous shaking is 5 to 8 minutes.

[0043] Furthermore, in step (C2), the mixed solution is dripped onto the surface of the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance of the present invention at a concentration of 15 to 20 uL / cm 2 .

[0044] Furthermore, in step (C2), bisphenol A is removed by soaking in a methanol and acetic acid solution with a volume ratio of (40-50):1.

[0045] The application of the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance described in the present invention or the imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO described in the present invention in the detection of bisphenol A.

[0046] Furthermore, the detection process includes the following steps:

[0047] MIP / Ag2S / Bi2O3@Bi2S3 / FTO was immersed in a mixed solution of methanol and water of bisphenol A, incubated, rinsed with deionized water, and placed in a PBS aqueous solution containing ascorbic acid (AA) to examine its amperometric response, and compared with MIP / Ag2S / Bi2O3@Bi2S3 / FTO before incubation in a mixed solution of methanol and water of bisphenol A. The current difference before and after incubation was used to achieve quantitative analysis of bisphenol A.

[0048] Furthermore, the incubation time is more than 20 minutes.

[0049] Furthermore, ascorbic acid (AA) was used as a cavitation scavenger in the detection of BPA.

[0050] Furthermore, the time for eluting bisphenol A with a mixed solution of methanol and acetic acid is 6 to 10 minutes.

[0051] In this study, Ag2S / Bi2O3@Bi2S3 photoactive materials were prepared by combining the low-temperature water bath method and the in-situ ion layer adsorption method. This assembly strategy can not only effectively promote charge separation, but also make full use of light energy and improve the photoelectric conversion efficiency. Then, a molecular imprinting polymer MIP was prepared by a simple thermally initiated free radical polymerization reaction and further constructed, and the MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor was obtained. After the template molecule BPA was eluted, the polymer film left a cavity that could specifically recognize BPA. After re-incubation with BPA, the BPA molecules occupied the cavity again, making the photocurrent value of the test smaller. In addition, during the photocurrent test, ascorbic acid (AA) was used as a hole scavenger to inhibit the recombination of photogenerated electron-hole pairs. Quantitative detection of BPA can be achieved based on the change in photocurrent.

[0052] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0053] (1) The present invention uses silver sulfide to sensitize the Bi2O3@Bi2S3 heterostructure to form an Ag2S / Bi2O3@Bi2S3 ternary heterojunction. Due to the stronger synergistic effect between the multi-component substances, the separation efficiency of electron-hole pairs is further improved. The stability of the ternary heterostructure is also significantly improved compared to the binary system. The introduction of Ag2S can effectively prolong the lifetime of photogenerated carriers, thereby increasing the rate of photocatalytic reaction.

[0054] (2) The present invention adopts a one-step water bath method to synthesize the Bi2O3@Bi2S3 heterostructure, and then introduces Ag2S through an improved in situ ion layer adsorption method to synthesize Ag2S / Bi2O3@Bi2S3 / FTO. The synthesis method is simple, efficient, low-cost and easy to operate.

[0055] (3) The present invention combines molecular imprinting to construct the MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor, which has a simple and efficient construction process and can sensitively detect and identify the target bisphenol A. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 The scanning electron microscope spectra of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO, Ag2S / Bi2O3@Bi2S3 / FTO and MIP / Ag2S / Bi2O3@Bi2S3 / FTO;

[0057] Figure 2 Energy scattering spectra of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO;

[0058] Figure 3 X-ray electron energy spectra and ultraviolet diffuse reflectance spectra of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO;

[0059] Figure 4 This is the X-ray photoelectron energy spectrum analysis diagram of Ag2S / Bi2O3@Bi2S3;

[0060] Figure 5 X-ray electron energy spectrum of Bi 4f, O 1s, S2p, S2s, C 1s and Ag 3d of Ag2S / Bi2S3@Bi2O3;

[0061] Figure 6 The photocurrent response diagrams of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO under visible light;

[0062] Figure 7 The photocurrent response diagrams of Ag2S / Bi2O3 / FTO, Ag2S / Bi2S3 / FTO and Ag2S / Bi2S3@Bi2O3 / FTO under visible light;

[0063] Figure 8 Photoelectrochemical test diagram of MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor in detecting different concentrations of bisphenol A;

[0064] Fig. 9 The chemical structures of BPA and its structural analogs and the effect diagram of the specific recognition of bisphenol A by Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance;

[0065] Fig.10 The effect diagram of optimizing different conditions to prepare Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance for detecting bisphenol A, where A is the optimization result of silver nitrate concentration, B is the optimization diagram of the ratio of template molecules and functional monomers, C is the optimization diagram of elution time, and D is the optimization diagram of incubation time. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0067] Example 1

[0068] 1. Add 0.2332g Bi(NO3)3 .5H2O was added to a nitric acid aqueous solution (125μL HNO3+5mL H2O) and stirred vigorously to obtain a precursor solution labeled as solution A. At the same time, 0.1248g hexadecyltrimethylammonium bromide (CTAB) and 0.0698g thioacetamide (TAA) were added to 60mL H2O and ultrasonically mixed, labeled as solution B. Subsequently, solution A was added dropwise to solution B while stirring vigorously at 30°C for 3h. The precipitate was washed twice by centrifugation with water and ethanol, respectively, and dried at 60°C to obtain Bi2O3@Bi2S3.

[0069] As a comparison, Bi2O3 nanosheets were synthesized by the same method without adding TAA.

[0070] As a comparison, Bi2S3 nanosheets were synthesized by adding an excess of TAA (0.1396 g) using the same method.

[0071] 2. Ultrasonic dispersion of Bi2O3@Bi2S3, Bi2O3, and Bi2S3 in deionized water at a concentration of 5 mg / mL was performed to obtain dispersions. Then, 20 μL of the dispersions were dropped on clean and dry FTO conductive glass, and the drop coating area was fixed to 1 cm 2 . After the electrodes were dried, Bi2O3@Bi2S3 / FTO, Bi2O3 / FTO and Bi2S3 / FTO electrodes were obtained respectively. 15μL of AgNO3 solution (20mmol / L) was dropped on the surfaces of Bi2O3@Bi2S3 / FTO, Bi2O3 / FTO and Bi2S3 / FTO electrodes respectively, and reacted in the dark for 30 minutes. Then, 15μL of Na2S solution (20mmol / L) was dropped on the surfaces of the three electrodes after the reaction respectively. After reacting for 30 minutes, the unreacted reagents were removed with deionized water. After drying, Ag2S / Bi2O3@Bi2S3 / FTO, Ag2S / Bi2O3 / FTO and Ag2S / Bi2S3 / FTO electrodes were obtained respectively.

[0072] 3. Dissolve 0.1mmol bisphenol A (BPA), 0.3mmol methacrylic acid (MAA) and 0.1mmol styrene (ST) in 10mL N,N-dimethylformamide (DMF) and stir for 3h to fully form hydrogen bonds between the template molecule BPA and the functional monomers MAA and ST. Then, add 1.5mmol ethylene glycol dimethacrylate (EGDMA) and 10mg azobisisobutyl ester (AIBN) to the above solution, stir magnetically for 10min, and degas with N2 for 30min. Transfer the mixed solution to 60℃ and heat for 3h until a colorless and opaque molecular imprinting polymer MIP solution is obtained.

[0073] The above method is adopted, except that BPA is not added, and the rest is the same to obtain a NIP solution.

[0074] 100 μL of the prepared MIP and NIP solutions were mixed with 900 μL of DMF solution containing 3 mg of polyvinylidene fluoride (PVDF), respectively. The mixture was then vigorously shaken for 5 min. Finally, 15 μL of the mixed solution was drop-coated on the surface of the Ag2S / Bi2O3@Bi2S3 / FTO electrode. The drop-coating area was fixed at 1 cm 2 The obtained electrode was dried at 60°C, and then soaked in methanol:acetic acid (40:1, v / v) for 2-10 min to remove BPA. After washing and drying, MIP / Ag2S / Bi2O3@Bi2S3 / FTO and NIP / Ag2S / Bi2O3@Bi2S3 / FTO photoelectrochemical sensors were obtained.

[0075] The Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO, Ag2S / Bi2O3@Bi2S3 / FTO and MIP / Ag2S / Bi2O3@Bi2S3 / FTO obtained in this embodiment were analyzed by scanning electron microscope. Figure 1 shown. Figure 1 Scanning electron microscope images of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO, Ag2S / Bi2O3@Bi2S3 / FTO and MIP / Ag2S / Bi2O3@Bi2S3 / FTO, among which A is Bi2O3 / FTO, B is Bi2O3@Bi2S3 / FTO, C is Ag2S / Bi2O3@Bi2S3 / FTO, and D is MIP / Ag2S / Bi2O3@Bi2S3 / FTO. Figure 1 A shows the SEM image of Bi2O3 nanosheets, which have a smooth, neat surface and are highly dispersed. Figure 1 B shows that the surface of the composite material Bi2O3@Bi2S3 sample becomes rough and wrinkled after the introduction of the sulfiding agent Bi2S3. Figure 1 C shows that after the introduction of Ag2S, the surface roughness of the nanosheets is greatly increased, which indicates that Ag2S is anchored on the Bi2O3@Bi2S3 surface in large quantities. Then the recognition unit MIP is further introduced, such as Figure 1 As shown in Figure D, the surface of the nanosheet-shaped Ag2S / Bi2O3@Bi2S3 is covered with a thin film, which verifies the successful construction of the MIP-PEC sensor based on Ag2S / Bi2O3@Bi2S3.

[0076] Energy dispersive spectroscopy analysis was performed on the Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO obtained in this embodiment. The results are as follows: Figure 2 shown. Figure 2 Energy scattering spectra of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO, where A is Bi2O3 / FTO, B is Bi2O3@Bi2S3 / FTO, and C is Ag2S / Bi2O3@Bi2S3 / FTO. Figure 2 A corresponds to the EDS element mapping of Bi2O3 / FTO. In contrast, Figure 2 B shows that the added S element was found in the EDS element mapping of Bi2O3@Bi2S3 / FTO, verifying that Bi2S3 was successfully introduced. Figure 2 C analyzed the Ag2S / Bi2O3@Bi2S3 / FTO after the introduction of Ag2S, and found that the Ag element increased compared with Bi2O3@Bi2S3 / FTO in the corresponding EDS element mapping, proving the successful introduction of Ag2S. The above EDS element mapping test results verified the successful synthesis of Bi2O3@Bi2S3 and Ag2S / Bi2O3@Bi2S3 composites.

[0077] The Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO obtained in this embodiment were analyzed by X-ray electron spectroscopy and ultraviolet diffuse reflectance spectroscopy. Figure 3 shown. Figure 3 The X-ray electron energy spectrum and ultraviolet diffuse reflectance spectrum of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO are shown in Figure 1. Among them, A is the XRD diagram of Bi2O3, B is the XRD diagram of Bi2O3@Bi2S3, C is the XRD diagram of Ag2S / Bi2O3@Bi2S3, and D is the ultraviolet diffuse reflectance spectrum of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO (a is Bi2O3 / FTO, b is Bi2O3@Bi2S3 / FTO, and c is Ag2S / Bi2O3@Bi2S3 / FTO). The XRD spectrum of Bi2O3 is shown in Figure 1. Figure 3 A, the main peak intensity of Bi2O3 is weak, indicating that the prepared Bi2O3 has low crystallinity, because it is difficult to obtain Bi2O3 with high crystallinity without further heat treatment and annealing process. The peaks of 32.46°, 46.43°, 55.09° and 77.29° correspond to the (111), (200), (220), (311), (400) and (420) planes of Bi2O3 (JCPDS No.27-0052). For Bi2O3@Bi2S3( Figure 3B), the diffraction peaks at 24.94° and 40.08° are attributed to Bi2S3 (JCPDS No.17-0320). In addition, in the heterojunction Bi2O3@Bi2S3, the main diffraction peaks of Bi2O3 still exist. Finally, XRD characterization of Ag2S / Bi2O3@Bi2S3 / FTO was carried out. Figure 3 As shown in Figure C, the diffraction peak at 37.71° belongs to Ag2S (JCPDS No.17-0320), and the diffraction peaks at 26.61°, 61.73°, and 65.74° belong to FTO conductive glass. All observed peaks confirm the successful construction of the proposed Ag2S / Bi2O3@Bi2S3 / FTO photoelectrode. The optical properties of the photoelectrode were evaluated by recording the ultraviolet diffuse reflectance spectra (UV-vis DRS) of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO, and Ag2S / Bi2O3@Bi2S3 / FTO, as shown in Figure 5C. Figure 3 D. Bi2O3 / FTO (curve a) has weak absorption of visible light. After the introduction of Bi2S3, the absorption of Bi2O3@Bi2S3 / FTO (curve b) undergoes a significant red shift. After the further introduction of Ag2S, the light absorption of the Ag2S / Bi2O3@Bi2S3 composite material increases more significantly due to the inherent optical activity of Ag2S. The in-situ grown Ag2S has a narrow band gap, resulting in less required electron transition energy. The Ag2S / Bi2O3@Bi2S3 / FTO composite material easily generates photogenerated electron holes under visible light irradiation, which significantly enhances its visible light activity.

[0078] The Ag2S / Bi2O3@Bi2S3 obtained in this embodiment was analyzed by X-ray photoelectron spectroscopy. Figures 4-5 shown. Figure 4 This is the X-ray photoelectron energy spectrum analysis diagram of Ag2S / Bi2O3@Bi2S3. Figure 4 It can be seen that Bi, O, Ag and S elements all exist in Ag2S / Bi2O3@Bi2S3. Figure 5 The XPS analysis diagram of Bi 4f, O 1s, S2p, S2s, C 1s and (F) Ag 3d of Ag2S / Bi2O3@Bi2S3, wherein A is Bi 4f of Ag2S / Bi2O3@Bi2S3, B is O1s of Ag2S / Bi2O3@Bi2S3, C is S2p ​​of Ag2S / Bi2O3@Bi2S3, D is S2s of Ag2S / Bi2O3@Bi2S3, E is C1s of Ag2S / Bi2O3@Bi2S3, and F is Ag 3d of Ag2S / Bi2O3@Bi2S3. Specifically, Figure 5A shows that the binding energies at 164.40 eV and 158.56 eV are similar to the Bi 4f 5 / 2 and Bi4f 7 / 2 For the Bi-S family, the peaks at 163.57 eV and 157.77 eV are related to the Bi 4f 5 / 2 and Bi 4f 7 / 2 Related. Figure 5 The other two peaks of C at 163.50 eV and 164.38 eV are derived from S2p 3 / 2 and S2p 1 / 2 , confirming the successful incorporation of sulfur into the product, and Figure 5 This is also confirmed by the peak of S2s at 225.19 eV in D. This sulfur incorporation is crucial to reduce the band gap and enhance the separation of photogenerated carriers in the product. Figure 5 B and Figure 5 E shows the high-resolution spectra in the O1s and C1s regions, corresponding to the Bi-O bond, CC bond, and CN bond, respectively. Figure 5 F shows the high-resolution spectrum of the Ag 3d region. 3 / 2 and Ag3d 5 / 2 The corresponding binding energies are 367.67 eV and 373.67 eV, respectively.

[0079] The photocurrent response of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO obtained in this embodiment was analyzed under visible light. The results are as follows: Figure 6 shown. Figure 6 Figure 2 is the photocurrent response diagram of Bi2O3 / FTO, Bi2O3@Bi2S3 / FTO and Ag2S / Bi2O3@Bi2S3 / FTO electrodes under visible light irradiation, where A is Bi2O3 / FTO, B is Bi2O3@Bi2S3 / FTO, and C is Ag2S / Bi2O3@Bi2S3 / FTO. Figure 6It is obvious that the photocurrent of Bi2O3 (curve a) is small. After the introduction of Bi2S3 (curve b), the photocurrent signal increases, which may be attributed to the formation of heterostructure. When Ag2S is in situ assembled on the electrode surface, compared with Bi2O3@Bi2S3 / FTO, Ag2S / Bi2O3@Bi2S3 / FTO (curve c) not only increases the photocurrent signal by nearly 9 times, but also from its photocurrent morphology, it can be seen that the recombination of carriers is obviously suppressed, and the photoelectric conversion efficiency is significantly improved. The above test results show that the formation of Ag2S sensitized heterostructure strongly promotes the transfer of charges, and the recombination of photogenerated electron-hole pairs is suppressed. The Ag2S / Bi2O3@Bi2S3 / FTO composite photoelectrode material synthesized by one-step water bath method combined with in situ ion layer adsorption method has excellent PEC performance, which provides a large and stable photocurrent for the subsequent introduction of recognition units to construct MIP-PEC sensors. The photocurrent response of Ag2S / Bi2O3 / FTO, Ag2S / Bi2S3 / FTO and Ag2S / Bi2S3@Bi2O3 / FTO obtained in this embodiment was analyzed under visible light. Figure 7 shown. Figure 7 The photocurrent response diagram of Ag2S / Bi2O3 / FTO, Ag2S / Bi2S3 / FTO and Ag2S / Bi2S3@Bi2O3 / FTO electrodes under visible light irradiation, where A is Ag2S / Bi2O3 / FTO, B is Ag2S / Bi2S3 / FTO, and C is Ag2S / Bi2O3@Bi2S3 / FTO. Figure 7 It is obvious that compared with Ag2S / Bi2S3 / FTO (curve b), Ag2S / Bi2O3 / FTO (curve a) has a smaller photocurrent, which may be attributed to the band gap and light absorption characteristics of Bi2S3 and Ag2S, which may be better than Bi2O3, and can absorb light in a longer range, effectively promoting the separation and migration of photogenerated charges, thereby generating more photocurrent. Ag2S / Bi2S3@Bi2O3 / FTO (curve c) still shows excellent photocurrent characteristics, which is due to the heterojunction characteristics of the three materials can effectively separate photogenerated electrons and holes, improve the mobility of carriers, and enhance photocurrent. The presence of Ag2S can further improve the band structure of the material and further improve the photoelectric performance.

[0080] Example 2 Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance is used to detect the content of bisphenol A

[0081] (1) The MIP / Ag2S / Bi2O3@Bi2S3 / FTO prepared in Example 1 was immersed in different concentrations (1×10 -7 mol / L、1×10 -8 mol / L、1×10 -9mol / L、1×10 -10 mol / L, and 1×10 -11 mol / L) of bisphenol A in methanol and water (methanol:water v / v, 1:9), incubated for 20 min, and rinsed with deionized water.

[0082] Finally, it was placed in a 10mmol / L PBS aqueous solution containing 0.1mol / L ascorbic acid (AA) to check its amperometric response. The bias voltage during the test was 0.0V (vs Ag / AgCl). Among them, AA can capture photogenerated holes and inhibit the recombination of photogenerated electron-hole pairs. All amperometric responses were tested under visible light irradiation with a 20s switching cycle. And compared with MIP / Ag2S / Bi2O3@Bi2S3 / FTO before incubation in a mixed solution of methanol and water of bisphenol A. The photocurrent of MIP / Ag2S / Bi2O3@Bi2S3 / FTO before incubation in a mixed solution of methanol and water (v / v, 1:9) of bisphenol A was I0, and the photocurrent after incubation in a mixed solution of methanol and water (v / v, 1:9) of bisphenol A with different concentrations was Is. Their difference was used to achieve quantitative analysis of BPA. The results are shown in Figure 8 shown.

[0083] The electrode obtained after incubation in a mixed solution of bisphenol A in methanol and water was immersed in a 10mmol / L PBS buffer containing 0.1mol / L ascorbic acid for photoelectrochemical measurement. The relationship between different concentrations of bisphenol A and the intensity of photoelectrochemical and electrochemical signals was obtained, and a curve was drawn with the logarithm of the concentration (lgC) as the abscissa and the photocurrent intensity (I) as the ordinate, and the curve was linearly fitted. The results are shown in Figure 8 shown.

[0084] Figure 8 The photoelectrochemical test diagram of MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor in detecting bisphenol A at different concentrations, where A is the photocurrent response diagram of MIP / Ag2S / Bi2O3@Bi2S3 / FTO electrode after identification in solutions containing different concentrations of BPA, and B is the linear calibration diagram of MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor. Figure 8 A shows that at 1×10 –11 mol / L~1×10 –7mol / L, with the increase of BPA concentration, the number of imprinted cavities occupied by BPA molecules increases, electron transfer is hindered, and the photocurrent response of the molecular imprinting sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO decreases accordingly. The photocurrent change value (ΔI) is defined as ΔI=I0–Is, where I0 and Is are the photocurrent signals corresponding to the mixed solution of methanol and water of bisphenol A before (I0) and after (Is), respectively. According to the test results, ΔI has a good linear relationship with the logarithm of BPA concentration. The calculation results show that the linear regression equation is ΔI(μA)=4.8756+0.4149lg C(mol / L)(R 2 =0.9917)(see Figure 8 B) The detection limit obtained by the determination was 4.29×10 –12 mol / L (the calculation formula is 3σ / k, where σ is the standard deviation of the blank sample and k is the slope of the calibration curve).

[0085] Example 3

[0086] In order to evaluate the specificity of the photoelectric film, common interferents in actual sample detection were selected, such as phenol (PhOH), hydroquinone (HQ), 2,4-dichlorophenol (2,4-DCP) and catechol (CT). The experimental process was the same as in Example 2.

[0087] The above-mentioned interfering substances were mixed with BPA in a ratio of 10:1 as incubation substances, and then the MIP / Ag2S / Bi2O3@Bi2S3 / FTO prepared in Example 1 was immersed in a 1×10 -7 The effects of these compounds were investigated by incubating the samples in a mixture of methanol and water (methanol:water v / v, 1:9) at 1 mol / L concentration for 20 minutes and then rinsing with deionized water. Fig. 9 shown.

[0088] Fig. 9 The chemical structures of BPA and its structural analogues and a diagram showing the specific recognition of bisphenol A by Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance, wherein A is the chemical structure of BPA and its structural analogues, and B is a diagram showing the specific recognition of bisphenol A by Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance. Fig. 9 Display, in 1×10 –7 In the presence of 1×10 mol / L interferent and BPA, the photocurrent response of the fabricated MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor was similar to that of the single 1×10 –8There is almost no significant difference in the photocurrent response value corresponding to mol / L BPA. It verifies that the MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor has high specificity for BPA recognition and has potential application prospects in actual detection.

[0089] In order to prove the applicability of the prepared MIP / Ag2S / Bi2O3@Bi2S3 / FTO PEC sensor for detecting BPA in practical applications, BPA was added to Wahaha bottled mineral water using the standard addition method for testing. The bottled water was purchased from a local supermarket and did not contain BPA. Subsequently, BPA was added at concentrations of 0.00pmol / L, 10.00pmol / L, 50.00pmol / L, 100.00pmol / L and 500.00pmol / L, and incubated for 20 minutes respectively, and rinsed with deionized water. The MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor prepared in Example 1 was used for quantitative testing. The results are shown in Table 1.

[0090] Table 1 Analysis results of tap water samples

[0091]

[0092] As shown in Table 1, the recovery test results were between 98.62%–104.43%, and the relative standard deviation (RSD) was less than 5%, which verified that the MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor was able to accurately determine BPA in actual sample analysis.

[0093] Example 4

[0094] The preparation of the MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor in this embodiment is basically the same as that in Example 1, except that the concentration of silver nitrate used in step 2 is adjusted to 10mmol / L, 15mmol / L, 20mmol / L, 25mmol / L and 30mmol / L, respectively, to obtain five groups of MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensors. The detection concentration is 1×10 –7 mol / L bisphenol A, the optimization results of silver nitrate concentration are as follows Fig.10 As shown in A, Fig.10As can be seen in Figure A, in the range of 10mmol / L to 20mmol / L AgNO3 concentration, the photocurrent of Ag2S / Bi2O3@Bi2S3 / FTO increases with the increase of AgNO3 concentration. However, in the range of 20mmol / L to 30mmol / L, the photocurrent of Ag2S / Bi2O3@Bi2S3 / FTO decreases with the increase of AgNO3 concentration, which may be because the excess Ag2S on the electrode surface hinders the charge transfer. Therefore, 20mmol / L was selected as the optimal concentration of AgNO3.

[0095] Example 5

[0096] The preparation of the MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor in this embodiment is basically the same as that in Example 1, except that the molar ratios of the template molecules bisphenol A, methacrylic acid and styrene in step 3 are 0.1:0.2:0.1, 0.1:0.3:0.1, 0.1:0.4:0.1, 0.1:0.5:0.1 and 0.1:0.6:0.1, respectively, to obtain five groups of MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensors. The detection concentration was 1×10 –7 mol / L of bisphenol A, such as Fig.10 As shown in B, Fig.10 B is the optimized diagram of the ratio of template molecules and functional monomers, Fig.10 As can be seen in Figure B, when the molar ratio is 0.1:0.3:0.1, the ΔI value reaches the highest. As the proportion of functional monomers continues to increase, the ΔI value decreases. This may be because the excess functional monomers lead to a reduction in BPA recognition sites. At this time, the functional monomers have a dominant effect on charge transfer. When the BPA content is too high, it is harmful to the formation of the molecular imprinting layer. Therefore, when the molar ratio of bisphenol A, methacrylic acid and styrene is 0.1:0.3:0.1, the MIP-PEC sensor with the best performance can be obtained.

[0097] Example 6

[0098] The MIP / Ag2S / Bi2O3@Bi2S3 / FTO sensor of Example 1 was used to detect bisphenol A. The experimental process was the same as that of Example 2, except that the concentration of the mixed solution of bisphenol A in methanol and water (methanol to water v / v, 1:9) was 1×10 -7 mol / L, the elution time of bisphenol A with methanol and acetic acid (methanol and acetic acid v / v, 40:1) was 2min, 4min, 6min, 8min and 10min respectively, and the incubation time with the mixed solution of bisphenol A in methanol and water (methanol and water v / v, 1:9) was 5min, 10min, 15min, 20min and 25min respectively. The results are shown in Fig.10 As shown in C and D. Fig.10 C in the middle is the optimization diagram of elution time. Fig.10 D in the figure is the optimization diagram of incubation time. Fig.10 As can be seen from Figure C, the ΔI value reaches its maximum when the elution time is 8 min, and when the elution time is further increased, the ΔI value decreases slightly. This may be because the excessively long elution time affects the photoelectric performance of the electrode. Fig.10 As can be seen in Figure D, with the increase of immersion time, the ΔI value of the sensor gradually increases and reaches the maximum value at 20 minutes, indicating that the recognition time is best at 20 minutes. After 20 minutes, the ΔI value does not change with the increase of recognition time, and BPA recognition reaches saturation. Therefore, the optimal recognition time of MIP / Ag2S / Bi2O3@Bi2S3 / FTO for BPA detection is 20 minutes.

Claims

1. An Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance, characterized in that: The Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance is a Bi2O3@Bi2S3 photoelectric film nanomaterial with Ag2S deposited on the surface.

2. The Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance according to claim 1, characterized in that: The preparation method of Bi2O3@Bi2S3 photoelectric thin film nanomaterial comprises the following steps: (A1) adding bismuth nitrate pentahydrate to a nitric acid solution and stirring vigorously to obtain a precursor solution A; (A2) adding hexadecyltrimethylammonium bromide and thioacetamide to water and mixing by ultrasonication to obtain solution B; (A3) Precursor solution A is added dropwise into solution B, stirred, centrifuged, washed, and vacuum dried to obtain Bi2O3@Bi2S3 nanomaterials.

3. The Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance according to claim 2, characterized in that: In step (A1), the solid-liquid ratio of bismuth nitrate pentahydrate and nitric acid solution is (0.2300-0.2332):5.25 g / mL, and the concentration of nitric acid solution is 2-5%. In step (A2), the mass ratio of hexadecyltrimethylammonium bromide, thioacetamide and water is (0.1200-0.1248):0.0698:

60.

4. The Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance according to claim 2, characterized in that: In step (A3), the stirring time is 3 to 3.5 hours, the stirring temperature is 30 to 40° C., the centrifugal speed is 6000 to 8000 r, the centrifugal time is 5 to 8 minutes, washing is performed with water and ethanol respectively, and vacuum drying is performed at 60 to 65° C. for 10 to 12 hours.

5. The method for preparing the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance according to any one of claims 1 to 4 comprises the following steps: (B1) Ultrasonic dispersion of Bi2O3@Bi2S3 photoelectric thin film nanomaterials in water to obtain a dispersion, drop the dispersion on FTO conductive glass, and dry it to obtain a Bi2O3@Bi2S3 / FTO electrode; (B2) Drop silver nitrate solution on the surface of Bi2O3@Bi2S3 / FTO electrode and react in the dark, drop sodium sulfide solution on the surface of Bi2O3@Bi2S3 / FTO electrode after reaction, continue reaction, wash and dry.

6. The preparation method according to claim 5, characterized in that: In step (B1), the concentration of Bi2O3@Bi2S3 in the dispersion is 4-5 mg / mL, and the dispersion is dropped on the FTO conductive glass at 15-20 uL / cm 2 In step (B2), the concentration of the silver nitrate solution is 20-22 mmol / L, and the silver nitrate solution is dropped on the FTO conductive glass at 15-20 uL / cm 2 The concentration of sodium sulfide solution is 20-22 mmol / L. The sodium sulfide solution is dropped on the FTO conductive glass at 15-20 uL / cm 2 The reaction time is 30 to 40 minutes.

7. An imprinting sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO, characterized in that: It is prepared by using the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance as described in any one of claims 1 to 4.

8. The method for preparing the imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO according to claim 7, characterized in that: The following steps are involved: (C1) dissolving bisphenol A, methacrylic acid and styrene in N,N-dimethylformamide and stirring; adding ethylene glycol dimethacrylate and azobisisobutyl ester, continuing to stir, degassing, and heating to react to obtain a MIP solution; (C2) Mix the MIP solution with an N,N-dimethylformamide solution containing polyvinylidene fluoride, shake vigorously, and drop the mixed solution onto the surface of the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance as described in any one of claims 1 to 4, dry, soak to remove bisphenol A, wash, and dry to obtain the imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO.

9. The preparation method according to claim 8, characterized in that: In step (C1), the molar ratio of bisphenol A, methacrylic acid and styrene is 0.1: (0.2-0.6): 0.1, the molar mass ratio of ethylene glycol dimethacrylate to azobisisobutyl ester is (1.2-1.6): 20 mmol / mg, the stirring time is continued for 10-15 min, the nitrogen is degassed for 30-35 min, and the heating reaction is reacted at 60-70° C. for 2.5-3 h. In step (C2), the volume ratio of the MIP solution to the N,N-dimethylformamide solution containing polyvinylidene fluoride is 100:900; the concentration of the N,N-dimethylformamide solution containing polyvinylidene fluoride is 3-4 mg / mL, the time of vigorous shaking is 5-8 min, and the mixed solution is drop-coated on the surface of the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance as described in any one of claims 1 to 4 at 15-20 uL / cm 2 , remove bisphenol A by soaking in a methanol and acetic acid solution with a volume ratio of (40-50):

1.

10. Use of the Ag2S / Bi2O3@Bi2S3 photoelectric film with recognition performance according to any one of claims 1 to 4 or the imprinted sensor MIP / Ag2S / Bi2O3@Bi2S3 / FTO according to claim 7 in the detection of bisphenol A.